Variations in utilisation of colorectal cancer services in South Australia indicated by MBS/PBS benefits: a benefit incidence analysis. (17th February 2022) - Lal, Anita; McCaffrey, Nikki; Gold, Lisa; Roder, David; Buckley, Elizabeth
Abstract: Objective : This study investigated variations in healthcare expenditure for colorectal cancer (CRC) patients in South Australia by socioeconomic position (SEP) and remoteness area. Methods : Benefits incidence analysis (BIA) was used to examine healthcare expenditure and utilisation in relation to CRC patients by SEP and remoteness areas. Utilisation data was obtained for patients diagnosed with CRC in 2003–2013 from a dataset linked to a population‐based cancer registry, Medicare Benefits Scheme (MBS), Pharmaceutical Benefits Scheme (PBS), hospital and death data. Concentration indices estimated the distribution of health expenditure on MBS, MBS palliative care, PBS and general practitioners. Costs of claims data and length of stay in hospital were used as indicators of healthcare utilisation. Results : The results indicated that MBS palliative healthcare services utilisation favoured the more advantaged groups for both SEP and remoteness area (Concentration index (CI)= 0.1681, t‐value=54.42 (SEP) and CI=0.1546, t‐value=41.64). MBS expenditure was also favourable to the more advantaged groups (CI: 0.0785 and 0.0493).PBS and MBS general practitioner expenditure were equal (−0.0093 to 0.0250). Conclusion : Overall MBS and PBS healthcare expenditure for CRC patients was close to equality, however utilisation of MBS‐funded palliative healthcare services was less concentrated in low SEP and more remote areas. Implications for public health : Whether the differences in palliative healthcare utilisation supplied by private providers are offset by other services requires investigation to determine if there is a need for initiatives to improve equality and give greater support to those who choose to die at home.